“Making the Difficult Choice”: Understanding Georgia’s Test-Based Grade Retention Policy in Reading - Huddleston, Andrew Prescott (Education Policy Analysis Archives, 2015)
The author uses Bourdieu’s concepts of field, capital, and habitus to analyze how students, parents, teachers, and administrators are responding to Georgia’s test-based grade retention policy in reading at one Georgia elementary school. In this multiple case study, the author interviewed, observed, and collected documents regarding ten fifth graders, their parents, teachers, and administrators. Within the field of test-based retention, the students and parents brought cultural, social, and economic capital that received little value, and they readily accepted that the Criterion-Referenced Competency Tests (CRCT) was trustworthy and retention was fair. However, believing that retaining students would ultimately reproduce the inequities the policy claimed to address, the teachers and administrators used an appeals procedure to ensure that retention was not based solely on test scores.